Effect of Model-Based Problem Solving on Error Patterns of At-Risk Students in Solving Additive Word Problems - Yan Ping Xin; Soo Jung Kim; Jingyuan Zhang; Qingli Lei; Büşra Yılmaz Yenioğlu; Samed Yenioğlu; Xiaojun Ma (MDPI AG, 2023)
Students with learning disabilities/difficulties in mathematics often apply ineffective procedures to solve word problems due to a lack of conceptual understanding of word problem solving, which results in poor mathematics performance and falling further behind the normal achievements of their peers. Current mathematics curriculum standards emphasize conceptual understanding in problem solving as well as higher-order thinking and reasoning, including all students. The purpose of this study was to evaluate the impact of a computer-assisted model-based problem-solving intervention program (MBPS) on elementary students' word problem-solving performance by analyzing the error patterns. Results indicate that after the MBPS intervention, participants significantly improved their problem-solving performance and made fewer errors in solving problems across a range of additive word problem situations. Specifically, the participating students made their attempt to represent the mathematical relation, decontextualized from the word problem story, in the model equation before solving the problem, rather than blindly applying an operation or relying on the "keyword" strategy as they did during the preassessment. Implications of the study are discussed in the context of the National Council of Teachers of Mathematics' calling for teaching big ideas to help students develop a deep understanding of mathematics knowledge.